Geography Matters in the Inca Empire - Melanie Waldron (Oxford, United Kingdom Capstone Global Library Ltd, 2015)
How do we know about the Incas? What were Inca towns and cities like? What was the "lost city of the Incas"? Geography Matters in the Inca Empire looks at how the Inca Empire changed through time and gives fascinating insights into many different aspects of Inca life through its geography. Read about how the mountainous Inca geography led to their development of terrace farming, how the Incas worshipped the mountain peaks as gods and how the size of their Empire meant they built thousands of miles of roads and bridges to connect their people.
Keywords: Non Fiction -- Non Fiction